Implementasi Penggunaan Modifikasi Sepatu Pre Walker untuk Menjaga Stabilitas Sendi Ankle dalam Upaya Pencegahan Gangguan Kaki Pronasi pada Anak - Yulius Agung Saputro; Antonius Tri Wibowo (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2025)
This research aims to develop and implement a modified pre-walker shoe prototype to maintain ankle joint stability in children aged 8–18 months and prevent postural disorders such as foot pronation. The second year of the research focused on small- and large-scale product trials and initial evaluation of its effectiveness. Results indicate that the product has the potential to help children maintain balance while learning to walk. This innovative shoe has high economic value and is multifunctional, safe for indoor and outdoor use, and is designed from soft, flexible, and anti-slip materials to maintain ankle joint stability and prevent foot pronation in children. Based on the research results, it can be concluded that the implementation of modified pre-walker shoes is an effective preventive measure against foot pronation disorders and an educational innovation for parents in supporting children's motor development. Keywords: stability, postural disorders, ankle joint, pre-walker shoe, children